2019
DOI: 10.1016/j.arr.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of non-pharmacological interventions to treat malnutrition in older persons: A systematic review and meta-analysis. The SENATOR project ONTOP series and MaNuEL knowledge hub project

Abstract: Efficacy of non-pharmacological interventions to treat malnutrition in older persons: A systematic review and meta-analysis. The SENATOR project ONTOP series and MaNuEL Knowledge Hub project,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 50 publications
3
42
0
Order By: Relevance
“…A systematic review and meta-analysis considered studies that only included older persons with malnutrition and found no beneficial effects of ONS in changing body weight, body mass index, MNA score, muscle strength, activities of daily living, Timed Up&Go test, quality of life and mortality. Results of other interventions (dietary counselling and ONS, ONS combined with exercise, new ONS nutrition delivery systems) were inconsistent [41]. Another systematic review that explored the role of exercise added to oral nutritional support reported improvements in muscle strength but not in any other outcome, however mostly based on low or very low quality evidence [42].…”
Section: Management Of Malnutritionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review and meta-analysis considered studies that only included older persons with malnutrition and found no beneficial effects of ONS in changing body weight, body mass index, MNA score, muscle strength, activities of daily living, Timed Up&Go test, quality of life and mortality. Results of other interventions (dietary counselling and ONS, ONS combined with exercise, new ONS nutrition delivery systems) were inconsistent [41]. Another systematic review that explored the role of exercise added to oral nutritional support reported improvements in muscle strength but not in any other outcome, however mostly based on low or very low quality evidence [42].…”
Section: Management Of Malnutritionmentioning
confidence: 99%
“…Besides positive effects on intake, positive effects on nutritional status are also reported, and a couple of studies also look at functional and clinical outcomes. Unfortunately, findings in this latter respect are inconsistent and often negative [21], and benefits were generally questioned just recently [41].…”
Section: Knowledge Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the original papers on the topic refer to malnutrition although upon inspection it is clear that the term refers more narrowly to PEM/undernutrition. PEM interventions vary in their ability to prevent or improve relevant and meaningful outcomes such as nutritional status, morbidity, functional status, and mortality [46]. As part of MaNuEL, quality assessments were conducted using Cochrane and GRADE criteria on 18 primary intervention studies taken from 17 systematic reviews.…”
Section: Pemmentioning
confidence: 99%
“…They also identified two randomized controlled trials that showed improvements in functional status (measured by TUG and activities of daily living) in the ONS treated group. The researchers concluded there is a clear need for welldesigned, randomized controlled trials that follow standard criteria for reporting interventions on relevant outcomes for treating the condition in older people [46].…”
Section: Pemmentioning
confidence: 99%